Implementation of a crossed-slit system for fast alignment of sealed polycapillary X-ray optics - Zymaková, Anna; Khakurel, Krishna; Picchiotti, Alessandra; Błachucki, Wojciech; Szlachetko, Jakub; Rebarz, Mateusz; Uhlig, Jens; Andreasson, Jakob (Journal of synchrotron radiation, 2020)
A new modification of a table-top laser-driven water-jet plasma X-ray source has been successfully implemented and commissioned at the Extreme Light Infrastructure (ELI) Beamlines user facility. In order to preserve the broadband nature of the source for spectroscopic experiments, a polycapillary lens was initially chosen as the focusing element. Generally, polycapillary X-ray optics have a narrow photon acceptance angle and small field of view, making alignment complicated and time-consuming. This contribution demonstrates a straightforward, reliable and reproducible procedure for aligning polycapillary focusing optics with broadband X-rays. The method involves a pre-alignment step where two X-ray slits are mounted orthogonally on opposite sides of a 3D-printed cylindrical polycapillary holder. This helps to precisely determine the optical axis of the X-ray beam. Subsequent mounting of the polycapillary in the pre-aligned holder with the slits removed allowed for immediate transmission of the X-ray photons through the optics and has provided a good starting point for fine alignment.
Keywords: polycapillaries; X-ray slits; X-ray focusing optics; alignment; X-ray sources